Sarcasm and music in Shona jakwara institution - Matiure, Perminus; Matiure, Rungamirai (Midlands State University, 2016)
The paper explores the interplay of sarcasm, threshing and music during threshing of finger millet (jakwara). In this paper the combination of work, rhythm and sarcasm (chihwerure) during jakwara is regarded as a tripartite system in which the social commentary phenomenon is enacted. Currently very few farmers are still conducting jakwara functions since maize has subsequently substituted finger millet (zviyo, mhunga and mapfunde) as a staple crop and as such very few farmers grow zviyo at a large scale. This paper will go a long way in availing the proceedings of such an extinct agricultural event as well as acting as a preservation measure. The study adopted an ethnographic paradigm in which fieldwork was carried out in Hwedza District south of Harare the capital city of Zimbabwe. Some of the information enshrined in the article is drawn from the researcher’s lived experiences as he is also a Zezuru by origin. Face-to-face interviews were carried out amongst the Shona people of Rapako village in Hwedza on issues concerning their perception on rhythm as it is articulated during jakwara. The findings indicated that the Shona people express rhythm, and personal feelings through work experiences and ceremonies. Jakwara is one such work ceremony in which a number of social aspects of the Shona are displayed. The most outstanding aspects are song, rhythm and sarcasm. It was also concluded that jakwara has become extinct in the Shona society hence the need to document it.